2020
DOI: 10.3390/ijms21030798
|View full text |Cite
|
Sign up to set email alerts
|

The β-Blocker Carvedilol Prevented Ultraviolet-Mediated Damage of Murine Epidermal Cells and 3D Human Reconstructed Skin

Abstract: The β-blocker carvedilol prevents ultraviolet (UV)-induced skin cancer, but the mechanism is unknown. Since carvedilol possesses antioxidant activity, this study investigated whether carvedilol prevents oxidative photodamage of skin, a precursor event in skin carcinogenesis. The effects of carvedilol, metoprolol (a β-blocker without antioxidant property), and 4-hydroxycarbazole (4-OHC, a carvedilol synthesis intermediate and a free radical scavenger) were compared on UV- or H2O2-induced cell death and reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Previous studies have indicated that the β-blocker carvedilol, commonly used to manage cardiovascular disorders such as hypertension and heart failure, showed promising activity in preventing chemical carcinogen and UV-induced skin carcinogenesis in vitro and in vivo [3,4]. The anticancer mechanisms for carvedilol involve multifunctional action including attenuating UV-induced oxidative stress, DNA damage, inflammation, and oncogenic signaling pathways [4,5]. Further supporting a role of carvedilol in cancer prevention, a population-based cohort study of 6771 individuals demonstrated that long-term use of carvedilol was associated with a reduced risk of several types of cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that the β-blocker carvedilol, commonly used to manage cardiovascular disorders such as hypertension and heart failure, showed promising activity in preventing chemical carcinogen and UV-induced skin carcinogenesis in vitro and in vivo [3,4]. The anticancer mechanisms for carvedilol involve multifunctional action including attenuating UV-induced oxidative stress, DNA damage, inflammation, and oncogenic signaling pathways [4,5]. Further supporting a role of carvedilol in cancer prevention, a population-based cohort study of 6771 individuals demonstrated that long-term use of carvedilol was associated with a reduced risk of several types of cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the unknown targets for carvedilol could have significant implications for understanding carcinogenesis and chemoprevention of cancer as well as the development of new cancer-preventive strategies. Thus far, studies examining the mechanism of action of carvedilol eliminated β-blockade (15) and likely eliminated scavaging ROS (28) as chemopreventive mechanisms. In this study, the R-carvedilol concentration-response curves generated from the soft agar colony formation assay suggest that there are either multiple binding sites displaying negative cooperation or multiple targets involved with varying affinities.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies reported that following carvedilol treatment, irradiated cells exhibited reductions in NF-κB and AP-1 activity, PGE 2 release and colony formation [89,90], whereas topical application in reconstituted human skin reduced inflammation markers such as COX-2 and TNF-α expression, as well as hyperplasia and apoptosis [91]. Furthermore, carvedilol treatment decreased inflammatory cytokines and CPDs in hairless mice when photocarcinogenesis is stimulated experimentally.…”
Section: Recent Discoveries In Pre-clinical Studies: Carvedilol and B...mentioning
confidence: 99%